Le Terme Indéterminé: Réflexions Sur Une Modalité (pas Si) Simple ! - Marchisio, Giacomo (The Canadian Bar Review, 2022)
This article examines “undefined” terms (art. 1512 CCQ), an oft-neglected topic in contract law. By leveraging judicial precedent concerning its application, the article identifies conditions for its application and proposes a structured analysis to help courts fix an appropriate term. The proposed analysis will also help to distinguish undefined terms from uncertain terms (art. 1510 CCQ), in the hopes of helping put an end to uncertainties.